Peristaltic transport of a generalized Burgers' fluid: Application to the movement of chyme in small intestine - Tripathi D.; Pandey S.K.; Das S. (My University, 2025)
The present investigation deals with the peristaltic transport of generalized Burgers' fluid with fractional element model in a channel. The analysis is carried out under long wavelength and low Reynolds number assumptions. An efficient mathematical tool, namely, Adomian decomposition method, is used to obtain the analytical approximate solutions of the fractional differential equation. The channel is governed by the propagation of sinusoidal waves that help the walls contract and relax but not expand beyond the natural boundary. The expressions of axial velocity, volume flow rate and pressure gradient are obtained. The effects of the fractional parameters and the material constants are discussed on pressure difference and the friction force across one wavelength. The comparative studies for various models of viscoelastic fluids such as fractional generalized Burgers' model, generalized Burgers' model, fractional Burgers' model and Burgers' model are performed. It is inferred that the movement of viscoelastic chyme with generalized Burgers' model through the small intestine is favorable in comparison to the movement of viscoelastic chyme with fractional generalized Burgers' model. © 2010 Elsevier Ltd. All rights reserved.